THE PRINCIPLE OF JUSTICE IN TRANSACTIONS BASED ON PROFIT AND LOSS SHARING IN SHARIA BANKS - Trisadini Prasastinah Usanti; A. Shomad; Ari Kurniawan (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2014)
In fund raising with mudharabah agreement only contain a clause about sharing profits alone, does not contain a clause about sharing losses because the losses in case the fund will be borne by LPS, and there is no clause about profit sharing or revenue sharing is used. At mudharabah and musharakah financing contain a clause on sharing profits and losses, although there is a clause that does not reflect justice. Dalam penghimpunan dana dengan perjanjian mudharabah hanya memuat klausul tentang berbagi keuntungan saja, tidak memuat klausul tentang berbagi kerugian karena apabila terjadi kerugian maka dana tersebut akan ditanggung oleh LPS, dan tidak ada klausul tentang profit sharing atau revenue sharing yang dipergunakan. Pada pembiayaan mudharabah dan pembiayaan musyarakah memuat klausul tentang berbagi keuntungan dan kerugian, meskipun masih ada klausul yang belum mencerminkan keadilan.